2007
DOI: 10.1021/es070264m
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Individual-Based Model of Microbial and Bioconversion Dynamics in Aerobic Granular Sludge

Abstract: Aerobic granular sludge is a novel compact biological wastewater treatment technology for integrated removal of COD (chemical oxygen demand), nitrogen, and phosphate charges. We present here a multiscale model of aerobic granular sludge sequencing batch reactors (GSBR) describing the complex dynamics of populations and nutrient removal. The macro scale describes bulk concentrations and effluent composition in six solutes (oxygen, acetate, ammonium, nitrite, nitrate, and phosphate). A finer scale, the scale of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 31 publications
1
95
1
2
Order By: Relevance
“…This indicated that the granules were unstable. However, this was inconsistent with the previous studies finding that glucose-fed aerobic granular sludge had a compact shape under a higher organic loading (15 kg COD/(m 3 ·d)), with the same MLSS as for R3 [26]. This was likely due to the organic loading threshold for the instability of aerobic granules depending on the varieties of substrates [27].…”
Section: The Stability Of Aerobic Granular Sludgecontrasting
confidence: 79%
“…This indicated that the granules were unstable. However, this was inconsistent with the previous studies finding that glucose-fed aerobic granular sludge had a compact shape under a higher organic loading (15 kg COD/(m 3 ·d)), with the same MLSS as for R3 [26]. This was likely due to the organic loading threshold for the instability of aerobic granules depending on the varieties of substrates [27].…”
Section: The Stability Of Aerobic Granular Sludgecontrasting
confidence: 79%
“…The underlying assumptions are described and justified in detail elsewhere (40,(43)(44)(45), and empirical tests have demonstrated the framework's ability to make accurate predictions for real biological systems (46,47).…”
Section: Resultsmentioning
confidence: 99%
“…These phenomena particularly redefine the oxic-anoxic zones within granules which are important for simultaneous nitrogen and phosphorus removal. Although computationally demanding (37) and challenging from the standpoint of experimentally measuring all relevant parameters, these models should allow the virtual engineering of granules, which would without a doubt be a fascinating achievement.…”
Section: Discussionmentioning
confidence: 99%